Design of an often cost affective wind power system for a remote Bangladesh locality - Mirza, Rifat; Hossain, Maria; Hossain, Ashraf (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.